Community empowerment through plastic bottle upcycling training in Kampung Pueh Sematan, Kuching, Sarawak - Hanum Mukti Rahayu; Mahwar Qurbaniah; Nuri Dewi Muldayanti; Arif Didik Kurniawan; Khairunnisa Ibrahim (Universitas Hamzanwadi, 2025)
Plastic bottle waste is a persistent problem in Kampung Pueh Sematan, Kuching, Sarawak, where limited waste services and low environmental literacy often lead to open dumping or burning. This community service program aimed to improve residents’ understanding of plastic waste impacts and develop practical upcycling skills to transform used bottles into functional, value-added handicrafts. The program was conducted on 9 August 2025 at Surau Baitul Quddus through collaboration between Universitas Muhammadiyah Pontianak and I-CATS University College, involving 63 participants (10 local residents; 25 from I-CATS; 28 from Universitas Muhammadiyah Pontianak). Using a participatory empowerment approach, activities followed three stages: (1) awareness and socialization on environmental and health risks of unmanaged plastic waste, (2) hands-on training on sorting, cleaning, cutting, assembling, and decorating bottles, and (3) evaluation using a structured questionnaire. Participants produced items such as decorative lamps, storage containers, and reusable accessories. Questionnaire results were strongly positive: 100% reported no prior similar training; material clarity was rated 50% strongly agree and 50% agree; confidence to apply skills independently reached 33% strongly agree and 64% agree; perceived benefits were 100% (50% strongly agree; 50% agree); overall satisfaction was 42% strongly agree and 58% agree; and facility adequacy was 16% strongly agree and 84% agree. Overall, the program indicates that combining contextual environmental education with hands-on practice can support community readiness for sustainable plastic bottle upcycling and small-scale creative economic potential